Therapeutic and Diagnostic Applications of Multimetallic Rhenium(I) Tricarbonyl Complexes. Issue 14 (2nd March 2021) - Huang, Zhouyang; Wilson, Justin J.
Abstract: By virtue of their favorable properties, rhenium(I) tricarbonyl (Re(CO)3 ) complexes have arisen as novel therapeutic agents and cellular imaging probes for addressing problems of biomedical relevance. Although great success has been found in monometallic complexes of this type, there has been recent interest in developing multimetallic compounds containing Re(CO)3 moieties to capitalize on the potential synergistic effects of different metal centers. This Minireview provides an overview of multimetallic Re(CO)3 complexes that have been developed specifically for biomedical applications. The promising therapeutic and diagnostic potential of such complexes and future needs in this field are discussed. Abstract : Given the valuable therapeutic and diagnostic properties of the Re(CO)3 core, there has been a significant interest in using this fragment in conjunction with other metal centers. In this Minireview, we provide an overview of both homonuclear and heteronuclear multimetallic Re(CO)3 complexes that have been investigated for biomedical applications.